PROBLEMATIKA PENYELESAIAN PERKARA HADANAH DI PENGADILAN AGAMA KELAS 1 A PALEMBANG - Huzaimah, Arne (Nurani, 2013)
Abstrak: Where there is sugar there must be an ant, or like fishand water, as it were appropriate parable likens the Law andSociety, because where there is society there must be laws willbe needed. Law and society are two sides of which are difficultto separate, because they will need each other and influenceeach other.ملخص:حیث یوجد السكر یجب أن یكون ھناك نملة، أو مثل السمك والماء، كما انھاكانت مناسبة المثل یشبھ القانون والمجتمع، وذلك لأن عندما یكون ھناك مجتمع یجبأن یكون ھناك وستكون ھناك حاجة القوانین .القانون والمجتمع وجھان لوالتي یصعبفصل، لأنھا سوف نحتاج إلى بعضنا البعض وتؤثر على بعضھا البعض.Kata Kunci: hadanah, perceraian